Dementia and Atrial Fibrillation: Pathophysiological Mechanisms and Therapeutic Implications - Chopard, Romain; Piazza, Gregory; Gale, Seth Alan; Campia, Umberto; Albertsen, Ida Ehlers; Kim, Jisoo; Goldhaber, Samuel Z (The American journal of medicine, 2018)
Atrial fibrillation increases the risk of stroke by a factor of four- to fivefold, and dementia is a common consequence of stroke. However, atrial fibrillation has been associated with cognitive impairment and dementia, even in patients without prior overt stroke. Nonischemic mechanisms include cerebral hypoperfusion, vascular inflammation, brain atrophy, genetic factors, and shared risk factors such as age or hypertension. Critical appraisal of studies evaluating the association between atrial fibrillation and dementia in stroke-free patients reveals that several suffer from methodological issues, such as not including silent stroke or anticoagulation therapy in multivariate analyses. Some studies show a close relationship between atrial fibrillation and dementia due to silent stroke, in the absence of overt stroke. Evidence is accumulating that anticoagulation may be effective to decrease the risk of dementia in atrial fibrillation patients. Overall, the pathogenesis linking atrial fibrillation to dementia is likely multifactorial. Cerebral infarctions, including silent stroke, play a central role. These findings underscore the importance of stroke prevention measures in atrial fibrillation patients.